Adolescents with a diagnosis of anorexia nervosa: Parents' experience of recognition and deciding to seek help. (January 2014) - Thomson, Samuel; Marriott, Michael; Telford, Katherine; Law, Hou; McLaughlin, Jo; Sayal, Kapil
Background: Adolescents with anorexia nervosa rarely present themselves as having a problem and are usually reliant on parents to recognise the problem and facilitate help-seeking. This study aimed to investigate parents' experiences of recognising that their child had an eating problem and deciding to seek help. Methods: A qualitative study with interpretative phenomenological analysis applied to semi-structured interviews with eight parents of adolescents with a diagnosis of anorexia nervosa. Results: Parents commonly attributed early signs of anorexia nervosa to normal adolescent development and they expected weight loss to be short-lived. As parents' suspicions grew, close monitoring exposing their child's secretive attempts to lose weight and the use of internet searches aided parental recognition of the problem. They avoided using the term anorexia as it made the problem seem 'real'. Following serial unsuccessful attempts to effect change, parental fear for their child's life triggered a desire for professional help. Conclusions: Parents require early advice and support to confirm their suspicions that their child might have anorexia nervosa. Since parents commonly approach the internet for guidance, improving awareness of useful and accurate websites could reduce delays in help-seeking.